2008
DOI: 10.2478/s11756-008-0162-4
|View full text |Cite
|
Sign up to set email alerts
|

Domain evolution in the GH13 pullulanase subfamily with focus on the carbohydrate-binding module family 48

Abstract: Glycoside hydrolase (GH) family 13 comprises about 30 different specificities. Four of them have been proposed to form the GH13 pullulanase subfamily: pullulanase, isoamylase, maltooligosyl trehalohydrolase and branching enzyme forming the seven CAZy GH13 subfamilies: GH13 8-GH13 14. Recently, a new family of carbohydrate-binding modules (CBMs), the family CBM48 has been established containing the putative starch-binding domains from the pullulanase subfamily, the β-subunit of AMP-activated protein kinase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 65 publications
2
44
0
Order By: Relevance
“…Three probes encoded enzymes involved in carbohydrate metabolism including an a-amylase family (glycoside hydrolase family 13) gene and a 1,3-beta-glucan synthase. Glycoside hydrolase family 13 is a family of starch modifying enzymes comprising around 30 different specificities, including isoamylases, glucan synthases, and pullunases (Machovic & Janecek 2008). Recent studies have indicated that some GH13 family enzymes in fungi may be involved in the synthesis or modification of alpha glucan in the fungal cell wall rather than starch degradation (Yuan et al 2008).…”
Section: Gene Expression In the Interaction Between Trametes Versicolmentioning
confidence: 99%
“…Three probes encoded enzymes involved in carbohydrate metabolism including an a-amylase family (glycoside hydrolase family 13) gene and a 1,3-beta-glucan synthase. Glycoside hydrolase family 13 is a family of starch modifying enzymes comprising around 30 different specificities, including isoamylases, glucan synthases, and pullunases (Machovic & Janecek 2008). Recent studies have indicated that some GH13 family enzymes in fungi may be involved in the synthesis or modification of alpha glucan in the fungal cell wall rather than starch degradation (Yuan et al 2008).…”
Section: Gene Expression In the Interaction Between Trametes Versicolmentioning
confidence: 99%
“…It precedes the catalytic (β/α) 8 -barrel-like domain. While LD and isoamylase have one CBM annotated as CBM48, 17 KpPUL and Bacillus acidopullulyticus pullulanase (BaPUL) contain both CBM41 and CBM48 domains. 18,19 All the endo α-1,6 glucoside hydrolases have a catalytic (β/α) 8 -like domain.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 It together with the residues 4-D and 5-E has been named a catalytic triad. 50 From the aligned active sites here, the main role of residue 7-D seems to be not a chemical one but to hold the sugar ring in position through hydrogen bonding with the 2-hydroxyl. Residue 4-R was mostly conserved, but was replaced by Lys in some GH-77 proteins.…”
Section: Resultsmentioning
confidence: 96%